2015
DOI: 10.1118/1.4922132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of XR‐RV3 GafChromic® films in standard laboratory and in clinical conditions and means to evaluate uncertainties and reduce errors

Abstract: The overall uncertainty associated with the use of XR-RV3 films to determine skin dose in the interventional environment can realistically be estimated to be around 20% (k = 1). This uncertainty can be reduced to within 5% if carefully monitoring scanner, film, and fitting-related errors or it can easily increase to over 40% if minimal care is not taken. This work demonstrates the importance of appropriate calibration, reading, fitting, and other film-related and scan-related processes, which will help improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 47 publications
0
59
0
Order By: Relevance
“…Calibration is mostly performed according to the manufacturer's recommendations, in air, with the higher dose rate (>1 Gy/min). However, according to Farah et al 18 , dose rate variation does not have influence on film calibration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Calibration is mostly performed according to the manufacturer's recommendations, in air, with the higher dose rate (>1 Gy/min). However, according to Farah et al 18 , dose rate variation does not have influence on film calibration.…”
Section: Discussionmentioning
confidence: 98%
“…Our study was performed with films white facing towards x-ray source, following ISP 295 recommendation. However, as some groups work using the other side facing the source, it would be interesting to evaluate the orange side facing source 18 . We used our flatbed scanner without uniformity correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The film pieces were irradiated to 16 air kerma values between 0 and 10 Gy using RQR8 standard beam quality 29 . The conversion of air kerma to absorbed dose to skin is considered to be equal to one 30 …”
Section: Methodsmentioning
confidence: 99%
“…Uncertainties related to the use of XR‐RV3 Gafchromic films for patient skin dose assessment in the interventional environment have been estimated in our previous work and published in Medical Physics 30 . It is shown that overall uncertainty of skin dose measurements using XR‐RV3 Gafchromic films ranges from 9% (k = 2) for tightly controlled measurement conditions, adequate laboratory calibrations and well‐defined readout protocol to 78% (k = 2) in the worst case scenario where the conditions of exposure, film handling, and readout are weakly controlled and where corrections for the relevant influence quantities are not made.…”
Section: Methodsmentioning
confidence: 99%